2010
DOI: 10.1002/humu.21310
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of missense mutations causing Snyder-Robinson syndrome

Abstract: The Snyder-Robinson syndrome is caused by missense mutations in the spermine sythase gene that encodes a protein (SMS) of 529 amino acids. Here we investigate, in silico, the molecular effect of three missense mutations, c.267G4A (p.G56S), c.496T4G (p.V132G), and c.550T4C (p.I150T) in SMS that were clinically identified to cause the disease. Single-point energy calculations, molecular dynamics simulations, and pKa calculations revealed the effects of these mutations on SMS's stability, flexibility, and interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(141 citation statements)
references
References 48 publications
7
130
1
Order By: Relevance
“…In addition, it was demonstrated computationally that H-bonding and/or salt bridge disruptions are almost always disease-causing if they are in close proximity to the active site [2123]. In many cases, the mutations were found to decrease the number of intramolecular H-bonds within a protein or the number of H-bonds that the protein makes with DNA or with the solvent [24, 25].…”
Section: Impact Of Mutations On Protein Structural Propertiesmentioning
confidence: 99%
“…In addition, it was demonstrated computationally that H-bonding and/or salt bridge disruptions are almost always disease-causing if they are in close proximity to the active site [2123]. In many cases, the mutations were found to decrease the number of intramolecular H-bonds within a protein or the number of H-bonds that the protein makes with DNA or with the solvent [24, 25].…”
Section: Impact Of Mutations On Protein Structural Propertiesmentioning
confidence: 99%
“…Consequently, several groups have analyzed the relationships between nsSNPs and their location in a folded protein (e.g., [Burke et al, 2007;Wang and Moult, 2001;. However, proteins do not function in isolation and therefore it is vital to follow a systems biology approach and consider the effect of any nsSNP in terms of the mechanism by which the mutated protein interacts with others [Gong et al, 2011;Schuster-Bockler and Bateman, 2008;Teng et al, 2009;Zhang et al, 2010]. We now have experimental data on protein interactions both in terms of identifying the interacting partners (the interactome) and having 3D structures for complexes.…”
mentioning
confidence: 99%
“…However, conformational rearrangement of the protein interface could alleviate some of these adverse structural changes. Modeling of the energetics of disease-causing nsSNPs at interfaces using energy calculations suggests that often there is very little difference in the free energy of association between the wild-type and the disease-causing variant due to conformational rearrangements [Teng et al, 2009] [Zhang et al, 2010]. Second, we examined common polymorphisms.…”
mentioning
confidence: 99%
“…Tomatsu et al (2005) and Rivera-Colón et al (2012) showed that missense mutations [also called non synonymous substitution (Zhang et al, 2010(Zhang et al, , 2012] are the most common cause of MPS IVA. It causes amino acid changes due to single nucleotide polymorphisms, which can drastically change protein structure and function.…”
Section: Resultsmentioning
confidence: 99%